PERAN BAITUL MAAL WAT TAMWIL (BMT) AMANAH UMMAH TERHADAP PENINGKATAN USAHA PEDAGANG KECIL DI PASAR KARAH SURABAYA - Puspa Indraswari; Qudsi Fauzi (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This study aims to analyze the role of BMT “Amanah Ummah” in empower the small traders. The research methods used in this research was case study qualitative method, using data collection techniques performed with conductive interviews and direct observation with the object of research. The result of this study indicate that BMT has been instrumental in increasing the business of small traders in Karah market. The business improvement from the small traders can be seen from the business turnover, business asset, business income and the stability of their business. The member of BMT in Karah market, on average has increased their business seen from their business volume, increasing of daily inventory such asequipment used for trade and revenues of their business income. REFERENCESAndriani. 2005. BAITUL MAAL WAT TAMWIL Konsep dan Mekanisme di Indonesia,  (online), Volume 14, No.2,http://idb2.wikispaces.com/file/view/rd2012.pdf, diakses 11 Oktober 2016. Buchori, Alma. 2009. Manajemen Bisnis syariah. Bandung: AlfabetaChaniago, A. Arifinal, dkk. 1995. Ekonomi 2. Bandung: Angkasa.Hutomo, Mardi Yatmo. 2000. Pemberdayaan Masyarakat dalam Bidang Ekonomi: Tinjauan Teoritik dan Implementasi.  Jakarta : BappenasJakarsih, Aan. 2008. Pengaruh Kemampuan Manejerial Pengusaha Terhadap Keberhasilan Usaha Pengusaha sepatu di Sentra Industri Kecil PersepatuanMoleong, Lexy J. 2000. Metode Penelitian Kualitatif. Bandung: PT Remaja RosdakaryaMuhammad. 2006. Bank Syariah Analisa Kekuatan, Kelemahan, Peluang dan Ancaman. Edisi Kedua. Yogyakarta: Ekonisia.Munawir. 2000. Analisis laporan Keuangan. Yogyakarta: Liberty.P3EI. 2008. Ekonomi Islam. Rajawali Press: Jakarta.Ridwan, Muhammad. 2004. Manajemen Baitul Maal Wat Tamwil (BMT). Yogyakarta: UII Press.Satria, Dias dkk. 2004. Strategi Pengembangan Lembaga Keuangan Mikro Syariah (BMT – Baitul Maal Wat Tamwil) Dalam Memberdayakan potensi Usaha Kecil. LKTMSitumorang, Lusia dkk. 2006. Usaha Kecil Menengah dan Pembangunan. Jakarta: Ghalia IndonesiaSudarsono, Heri, 2004. Bank Dan Lembaga Keuangan Syariah. Edisi Kedua. Yogyakarta: EkonisiaSugiyono.2009. Metode Penelitian Bisnis. Bandung: AlfabetaSuryana. 2003. Kewirausahaan. Jakarta: Salemba Empat.Tingkat Nasional Malang; Universitas Brawijaya.Triyuwono, Iwan dan Mohammad As’udi. 2001. Akuntansi Syari’ah Memformulasikan Konsep Laba dalam Konteks Metfora Zakat. Jakarta: Salemba EmpatTunggal, Amin Widjaja. 2002. Akuntasi Perusahaan Kecil & Menengah. Jakarta: PT Rineka Cipta.Umar, Husein. 2003. Metode Riset Komunikasi Organisasi. Jakarta: PT Gramedia Pustaka UtamaWidodo, Hertanto dkk. 1999. Panduan Praktis Operasional Baitul Maal Wat Tamwil. Bandung: Mizanwww.koperasisyariah.com (online) diakses pada tanggal 25 September 2016Yin, Robert. 2012. Studi kasus Desain dan Metode Jakarta: PT Raja Grafindo Persada.Zainul, Arifin.1999. Memahami Bank Syariah,Lingkup, Peluang, Tantangan dan Prospek. Jakarta: Alvabet.